A qualitative study of provider perspectives on the barriers to contraceptive use in Kaliro and Iganga Districts, Eastern Central Uganda - Constance Sibongile Shumba; Jonathan Miyonga; Judith Kiconco; Patrick Kerchan; Tonny Tumwesigye (Health for All Nations, 2016)
Background: Family planning confers unique benefits including preventing unintended pregnancies, improving maternal and child health outcomes, and increasing women's access to education and economic opportunities. However, Uganda has a low contraceptive prevalence rate of only 30%, and progress in improving maternal and child health outcomes is slow. Objective: This assessment explores community health workers' and facility-based health workers' qualitative perspectives on the use of contraceptives in the Iganga and Kaliro districts in Eastern Central Uganda. Methods: The baseline assessment used a qualitative approach with a focused sample of community- and facility-based health workers aged 20-60 years. Two focus group discussions with Community Health Workers and four key informant interviews with facility-based health workers were conducted. Thematic content analysis was done manually. Results: The main factors influencing contraceptive use in these communities were preference for large families, perceived inadequate knowledge of family planning and fear of side effects, inadequate spousal and family support, male domination and risk of violence, divorce and polygamy, inadequate human resource capacity and low motivation, and user fees. Conclusion: The study findings suggest that there is low use of contraceptives for family planning in the Kaliro and Iganga districts in Uganda. Recommendations include developing a strong focus in exploring policy options to build the capacities of trained health workers to offer long-term methods in order to increase the availability of family planning options. Family planning interventions should increase the availability of contraceptive methods using gender-sensitive strategies, including community mobilization.